Interleukin-4 (IL-4) enhances and soluble interleukin-4 receptor (sIL-4R) inhibits histamine release from peripheral blood basophils and mast cells in vitro and in vivo - B. Niggemann; T. Zuberbier; U. Herz; K. Enssle; U. Wahn; H. Renz (Mediators of Inflammation)
The aim of the study was to analyse the effect of interleukin-4 (IL-4) on allergen and anti-IgE mediated histamine release from basophils and human skin mast cells and to assess whether soluble recombinant interleukin-4 receptor (sIL4R) can inhibit these effects. Anti-IgE stimulated histamine release from peripheral blood basophils and mast cells of atopic donors was enhanced after preincubation with IL-4, whereas after preincubation with sIL-4R it was inhibited. These effects were even more pronounced when samples were stimulated with a clinically relevant allergen. In IL-4 preincubated skin mast cells, there was a similar enhancement of anti-IgE stimulated histamine release, which could again be inhibited by sIL-4R. The effects of IL-4 and sIL4R were dose- and time-dependent. Mice sensitized to ovalbumin and treated with soluble recombinant murine sIL-4R showed significantly reduced immediate-type cutaneous hypersensitivity responses compared with untreated mice. These in vivo effects were IgE independent, since there were no significant differences in total and allergen specific IgE/IgG1 antibody titres between treated and untreated mice. This indicates that IL4 exerts priming effects on histamine release by effector cells of the allergic response and that these effects are potently antagonized by soluble IL-4R both in vitro and in vivo.